Phylogeny of the genus Loxospora s.l. (Sarrameanales, Lecanoromycetes, Ascomycota), with Chicitaea gen. nov. and five new combinations in Chicitaea and Loxospora - Łucja Ptach-Styn; Beata Guzow-Krzemińska; James C. Lendemer; Tor Tønsberg; Martin Kukwa (MycoKeys, 2024)
Loxospora is a genus of crustose lichens containing 13 accepted species that can be separated into two groups, based on differences in secondary chemistry that correlate with differences in characters of the sexual reproductive structures (asci and ascospores). Molecular phylogenetic analyses recovered these groups as monophyletic and support their recognition as distinct genera that differ in phenotypic characters. Species containing 2’-O-methylperlatolic acid are transferred to the new genus, Chicitaea Guzow-Krzem., Kukwa & Lendemer and four new combinations are proposed: C. assateaguensis (Lendemer) Guzow-Krzem., Kukwa & Lendemer, C. confusa (Lendemer) Guzow-Krzem., Kukwa & Lendemer, C. cristinae (Guzow-Krzem., Łubek, Kubiak & Kukwa) Guzow-Krzem., Kukwa & Lendemer and C. lecanoriformis (Lumbsch, A.W. Archer & Elix) Guzow-Krzem., Kukwa & Lendemer. The remaining species produce thamnolic acid and represent Loxospora s.str. Haplotype analyses recovered sequences of L. elatina in two distinct groups, one corresponding to L. elatina s.str. and one to Pertusaria chloropolia, the latter being resurrected from synonymy of L. elatina and, thus, requiring the combination, L. chloropolia (Erichsen) Ptach-Styn, Guzow-Krzem., Tønsberg & Kukwa. Sequences of L. ochrophaea were found to be intermixed within the otherwise monophyletic L. elatina s.str. These two taxa, which differ in contrasting reproductive mode and overall geographic distributions, are maintained as distinct, pending further studies with additional molecular loci. Lectotypes are selected for Lecanora elatina, Pertusaria chloropolia and P. chloropolia f. cana. The latter is a synonym of Loxospora chloropolia. New primers for the amplification of mtSSU are also presented.